Repair Costs of Existing RC Buildings Damaged by the L'Aquila Earthquake and Comparison with FEMA P-58 Predictions. Issue 1 (February 2018) - Del Vecchio, Ciro; Di Ludovico, Marco; Pampanin, Stefano; Prota, Andrea
Recent seismic events are a unique opportunity to monitor and collect details of direct repair costs and the downtimes associated with massive reconstruction processes. This paper focuses on the actual repair costs of five RC buildings damaged by the 2009 L'Aquila earthquake. The repair costs for structural and nonstructural components that experienced different types of earthquake damage are discussed and then used as a benchmark for the predictions. The comparison at both the building and component levels revealed that the FEMA P-58 methodology is suitable, in general, for application to different types of building stock. Ad hoc upgrades to the FEMA fragility database for components that are typical of the Mediterranean area are required. When implementing the proposed modifications, a reasonable level of consistency is achieved in terms of actual and predicted repair costs (differences in the range of 30–48%). A discussion on the actual repair costs and the main differences with the predicted costs for infills and partitions, structural subassemblies, floor finishes, and other acceleration-sensitive nonstructural components is provided, along with suggestions for further improving.